Modern teacher and the challenges of the twenty-first century - Youssef, Fatma Moustafa Swilam (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to reveal how to prepare the teacher in light of the challenges of the twenty-first century and how can he Confrontation them?, The current study is based on a descriptive approach to monitoring the current reality of teacher preparation and the challenges it faces in the twenty-first century and How did the teacher prepare in the field of e-learning in terms of skills and competencies necessary for that field so that the teacher can meet these challenges and new developments In the modern era. The study results are summarized in terms of teacher preparation in the various disciplines, adequate preparation, whether it is before service or during it, and that the job of the teacher changes with the change of contemporary life and its requirements and then he has to adapt these changes in order to build a new generation, Whereas, The criteria for judging the level of education in any country is the level of teacher preparation and training programs, and this requires comprehensive preparation for the teacher, especially with the massive expansion in the amount of scientific and human knowledge. The study recommends that the teacher must keep abreast of everything new in his field, whether on the scientific or professional level, and acquire some skills and competencies that help to Keep up with the challenges of the twenty-first century and employ technology in the educational process.